An evaluation of the collection characteristics and usability factors of three nanoparticle samplers - Castano, Andrew, author; Tsai, Candace Su-Jung, advisor; Brazile, William, committee member; Clegg, Benjamin, committee member (Colorado State University. Libraries, 2017)
Occupational exposure to nanoparticles is a concern to occupational hygienists because of the potential health effects of exposure, the lack of standardized sampling methods and regulatory guidance for exposure limits. Exposure assessments for nanoparticles should include analysis of particles with an electron microscope to allow for identification of particle size, shape and composition. This study is the first to use multiple aerosols to compare the particle size fractions collected by three handheld nanoparticle samplers designed to use transmission electron microscope grids for particle collection. These include the Tsai diffusion sampler (TDS), electrostatic precipitator (ESP), and thermophoretic personal sampler (TPS). Aerosols of sodium chloride, ISO fine test dust, and aluminum oxide were tested and the particle size fractions collected by the nanoparticle samplers were compared. The TDS collected more particles in a wider size range for the lowest concentration aerosol. The ESP sampled for much shorter than the others but collected the most particles for two out of three aerosols. The usability questionnaire assessed all steps involved in sampler usage and rated the features of each device. The TDS and TPS were best suited for full shift sampling and the ESP best for short term. The TDS was the most affordable and has the potential to collect larger particles on a secondary filter. Overall, the TPS was the easiest device to use. Study results indicated that all samplers successfully collected three types of aerosols, with smaller differences in the size fractions they collected and larger differences in the number of particles per surface area of their collection media.